2017
DOI: 10.17261/pressacademia.2017.627
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological capital and emotional labor behaviors of employee in tourism sector

Abstract: Emotional labor behavior is defined as making design of own emotional properties of employees, so as to be in favor of the organization, who often are together with and interacting with their customers as a part of their job. Psychological capital that has been suggested based on the concepts of psychology and positive organizational behavior, focuses on the positive strengths of employees, and provides a competitive advantage against their competitors, keeping positivity in its center. As in many sectors, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this research, it has been concluded that general psychological capital levels of the employees have been positive above medium level, and while the most positive dimension was self-efficacy, the least positive dimension was optimism. Similarly, there are many studies urging that the psychological capital levels of hotel employees are high (Suna & Okun, 2019;Yücel, 2019;Çelik & Bilginer, 2018;Kumlu & Güçlü Nergiz, 2018;Yorulmaz & Yavan, 2018;Kaya, Atabay, & Alamur, 2017). As the employees show higher job performance when self-efficacy, the most positive dimension in the hotel enterprises, increases (Luthans & Yousseff, 2007), employing those with high self-efficacy is needed to increase job performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, it has been concluded that general psychological capital levels of the employees have been positive above medium level, and while the most positive dimension was self-efficacy, the least positive dimension was optimism. Similarly, there are many studies urging that the psychological capital levels of hotel employees are high (Suna & Okun, 2019;Yücel, 2019;Çelik & Bilginer, 2018;Kumlu & Güçlü Nergiz, 2018;Yorulmaz & Yavan, 2018;Kaya, Atabay, & Alamur, 2017). As the employees show higher job performance when self-efficacy, the most positive dimension in the hotel enterprises, increases (Luthans & Yousseff, 2007), employing those with high self-efficacy is needed to increase job performance.…”
Section: Discussionmentioning
confidence: 99%